Model Pengembangan Creative Wellness Tourism Berbasis Seni Batik di Laweyan, Surakarta - Bonifasia Yuniar Rifani, Bonifasia Yuniar Rifani (Rumah Jurnal UNEJ, 2025)
Touristic creative wellness is a recent, globally spreading travel trend that couples creativity with overall well-being. Surakarta, with the recognition in UNESCO Creative City Network in 2021, therefore has ample scope for developing this tourism industry with creative wellness and Kampung Batik Laweyan as one of the recognized ancient centers for batik making. The authors discuss herein how the creative wellness tourism model anchored on batik artistry aims to marry these three important variables: cultural values, therapeutic benefits, and sustainability principles in tourism. It therefore uses qualitative methods and case studies to set into perspective the historical importance of Laweyan today in its transformation as a creative cultural tourism area with unique characteristics of batik, workshops, and culinary activities. This model links wellness programs using batik therapy with health and art, hence creating opportunities for unique tourist experiences that will benefit not only the visitors themselves but also contribute to community interests. The outcome of this study will contribute to new wellness destinations with a twist while maintaining the rich culture of batik and uplifting local livelihoods